Estimation of foreign MNEs spillovers in Spain. Issue 5 (12th March 2019) - Barge-Gil, Andrés; López, Alberto; Núñez-Sánchez, Ramón
ABSTRACT: Using Spanish firm-level data, we estimate productivity effects of spillovers from foreign multinationals to domestic firms in both manufacturing and service sectors. We find evidence of a positive productivity effect from multinationals on domestic firms operating in the same industry. Analyzing inter-industry linkages, we find evidence consistent with positive productivity spillovers from forward linkages (i.e. from suppliers to buyers) and negative productivity spillovers from backward linkages (i.e. from buyers to suppliers). Our main results hold when analyzing differences between multinational and domestic firms, and for periods of economic growth and recession, although some differences arise. Interestingly, we find evidence supporting a positive role of spillovers during the last recession period.